SOCIO-ENVIRONMENTAL FACTORS AS DETERMINANTS OF EMOTIONAL AND SOCIAL WELL-BEING OF ADOLESCENTS IN FOSTER HOMES IN SOUTHWESTERN NIGERIA (2015)
Adolescents in Foster Homes (AFHs) often experience negative psychological and developmental problems, which have grave consequences on their Emotional Well-being (EWB) and Social Well-being (SWB), with an attendant effect on their future lifestyles. Previous studies have focused more on AFHs’ deviant behaviour, school adjustment and psychological well-being than on EWB and SWB as well as their predisposing factors. This study, therefore, determined the extent to which socio-environmental factors (peer influence, foster officials’ religious beliefs, media exposure, exposure to drug/substance use, neighbourhood characteristics, school climate and foster home climate) determined EWB and SWB of AFHs in Southwestern Nigeria. Descriptive survey research design was adopted. Purposive sampling procedure was used to select 27 foster homes (nine public, 18 private) from the six states in Southwestern Nigeria. A combination of stratified, proportionate and simple random sampling techniques were used to select 575 AFHs inmates (339 boys, 236 girls). Socio-environmental Factors Scale (r=0.72), Emotional Well-being Scale (r=0.65), Social Well-being Scale (r=0.67) and Adolescent Fostering Scale (r=0.69) were used for the data collection. These were complemented with four Group Key Informant Interviews involving Chief Welfare Officers and assistants of four of the foster homes, and three Focus Group Discussions with AFHs. Four research questions were answered and two hypotheses tested at 0.05 level of significance. Quantitative data were analysed using descriptive statistics, Pearson product moment correlation and multiple regressions, while qualitative data were content analysed. Socio-environmental factors significantly influenced the EWB and SWB of AFHs (F(6,568) = 8.37, R= .29), accounting for 8.0% and 11.0% in the variance of EWB and SWB respectively. Foster home climate (β= 0.16), foster officials’ religious beliefs (β= 0.15), school climate (β= 0.13), peer influence (β= 0.91), media exposure (β= 0.09), neighbourhood characteristics (β= -0.23) and exposure to drug/substance use (β= -0.01) had relative contributions to EWB and SWB of AFHs. Furthermore, the socio-environmental factors correlated positively with the indices of emotional well-being of the AFHs as follows: self-concept (r= 0.09), self-esteem (r= 0.08), behavioural control (r= 0.07), stress management skills (r= 0.06) and resilience skills (r=0.06). Also, socio-environmental factors correlated positively with the indices of SWB as follows: environmental management skill (r= 0.08), sustained relationships (r= 0.07), good school performance (r= 0.07), assertiveness skills (r= 0.06), good social interaction (r= 0.06) and good communication skills (r= 0.05). The fostered boys had better EWB and SWB (x̅= 57.0, 60.3) than the girls (x̅= 54.9, 56.6), while the girls (x̅= 22.1) exhibited good social skills and trust than the boys (x̅= 18.0). Also, the private fostered adolescents (x̅ = 18.0) exhibited signs of greater comfort than those in the public homes (x̅ = 15.9). The AFHs were faced with the problems of attachment disorder, unhealthy development and low academic achievement. Foster home climate, foster officials’ religious beliefs, school climate, peer influence and media exposure positively influenced the emotional and social well-being of adolescents in foster homes in Southwestern Nigeria. Therefore, better social environment should be constantly sustained in foster care to ameliorate negative development of inmates.